Chrysin enhances antitumour immunity response through the IL‐12‐STAT4 signal pathway in the B16F10 melanoma mouse model. (13th May 2022) - Lu, Ran; Wang, Shuang; Jiang, Shasha; Li, Chenglin; Wang, Yashuo; Li, Ling; Wang, Yunyang; Ma, Guixin; Qiao, Hongye; Leng, Zhe; Niu, Junyun; Tian, Zibin; et al.
Abstract: Chrysin (CHR) is a flavonoid with extensive pharmacological activity. The molecular formula of CHR is C15 H10 O4 . CHR is reported to have antioxidative, antitumour and antiviral functions. To evaluate its potential function as a vaccine adjuvant, we prepared a melanoma vaccine using a soluble protein extract of B16F10 melanoma cells as antigen and CHR as an adjuvant. The melanoma model was developed after two immunizations, and it was discovered that combining B16F10 soluble protein antigen‐mixed CHR vaccine could inhibit tumour growth in the mouse model, and the overall survival rate was higher than that of the B16F10 antigen vaccine alone. In vivo and in vitro experiments were conducted to determine whether CHR functioned as an adjuvant by activating antigen‐presenting cells (APCs). We discovered that CHR activated APCs both in vivo and in vitro and may enhance Th1 cell function by activating the IL12‐STAT4 signal pathway, thereby enhancing the antitumour response of cytotoxic T lymphocytes (CTLs) in vivo. Next, to verify the critical role of CD8 + T cells in suppressing melanoma development, we transplanted CD8 + T cells from immunized mice to B16F10 tumour‐bearing mice and discovered that the survival rate of tumour‐bearing mice was significantly prolonged. In summary, our experimental results indicate that CHR can be used as a potential adjuvant to enhance antigen immunogenicity, inhibit B16F10 tumour growth in mice and improve tumour immune response.